Primary Signet Ring Cell/Histiocytoid Carcinoma of the Eyelid: Clinicopathologic Analysis with Evaluation of the E-Cadherin/β-Catenin Complex and Associated Genetic Alterations - Maria Del Valle Estopinal; Lavinia P. Middleton; Bita Esmaeli; Keyur P. Patel; Sara Nowroozizadeh; Michelle D. Williams (Case Reports in Pathology)
Signet Ring Cell (SRC)/Histiocytoid carcinoma of the eyelid is a rare neoplasm that shares histological and immunohistochemical similarities with diffuse gastric cancer and breast lobular carcinoma. The CDH1 gene, which encodes the E-cadherin protein, is the best known gene associated with these tumors. The structural and functional integrity of E-cadherin is regulated by interconnecting molecular pathways which might participate in the development of this disease. Hence, we analyzed the protein expression in key genes in E-cadherin-related pathways associated with primary SRC/Histiocytoid carcinoma of the eyelid. SRC/Histiocytoid carcinoma diagnosed in the eyelid/orbit at MD Anderson Cancer Center from 1990 to 2016 were evaluated. Clinicopathologic findings were studied to confirm the primary site of origin. Immunohistochemical studies for the expression of E-cadherin, β-catenin, c-Myc, Cyclin D1, Src, and p53 were analyzed. Next generation sequencing for the detection of somatic mutations was performed on each tumor with matched normal tissue, examining 50 cancer-related genes. Four primary SRC/Histiocytoid carcinomas of the eyelid were diagnosed in four male patients aged 40-82 years. Immunohistochemically, two tumors with loss of E-cadherin expression had weak β-catenin and low cytoplasmic staining for Src while the other two cases with intact E-cadherin showed strong β-catenin expression and high cytoplasmic expression for Src. Cyclin D1 was focally positive in three cases. Somatic mutations in CDH1, PIK3CA, and TP53 genes were detected in two cases. Our results suggest an abnormality in the convergence of E-cadherin/β-catenin pathways which may promote tumorigenesis by inducing expression of oncogenes such as Cyclin D1 and C-Myc. Mutations in CDH1, PIK3CA, and TP53 genes could induce E-cadherin dysfunction which takes part in the development and progression of this malignancy.